HUBUNGAN KUTU DOMPOLAN DYSMICOCCUS BREVIPES (CKLL.) (HOMOPTERA : PSEUDOCOCCIDAE) DAN SEMUT API SOLENOPSIS SP. (HYMENOPTERA: FORMICIDAE) PADA DUA CARA BERTANAM NENAS - Rosma Hasibuan . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2005)
Association of mealybug, Dysmicoccus brevipes (Ckll.) (Homoptera: Pseudococcidae) and fire ant, Solenopsis sp. (Hymenoptera: Formicidae) on two pineapple–planting patterns. A pineapple mealybug, Dysmicoccus brevipes (Ckll.) (Homoptera: Pseudococcidae) is an important insect pest in major pineapple growing areas. Its feeding activity causes damage on the pineapple plants and it can also transmit pineapple wilt virus. The mealybugs are often found in association with fire ants, Solenopsis sp. (Hymenoptera: Formicidae) that provide protection in exchange for the sweet honeydew liquid. The field study was conducted to determine the close association between mealybugs and fire ants on two plant row spacing (single and double row spacing) four different plant stages (3, 7, 11, and 17 months after planting). The results indicated that there was a significant correlation between the mealybugs and the fire ant on two pineapple-planting patterns, particularly on late growth periods (11, and 17 months after planting). In this field study, population of mealybugs on double row spacing were more abundant (ranging from 0 to 25.67 bugs/plant) compared with that on single row spacing which ranged 0 to 3.67 bugs/plant. Moreover, general mean of population density of mealybugs (14.53 bugs/plant) on double row was significantly higher than that on single row spacing (1.83 bugs/plant). In line with this mealybug-population development, mean numbers of fire ants caught on baited-sticky traps were ranged from 0 to 8.53 ants/trap on single row versus 0 to 23.57 ants/trap on double row spacing pattern. The general mean number of captured ants (12.73 ants/trap) on double row was significantly higher compared with that on single row spacing (5.55 ants/trap). It appears that the patterns of population densities of mealybugs are closely related to that of fire ants that act as attendant species on two pineapple row spacing.